Magnetic resonance spectroscopy to assess hepatic steatosis in patients with lipodystrophy - Canan Altay; Mustafa Seçil; Süleyman Cem Adıyaman; Başak Özgen Saydam; Tevfik Demir; Gülçin Akıncı; Ilgın Yıldırım Simsir; Erdal Eren; Ela Temeloğlu Keskin; Leyla Demir; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Lipodystrophy is a rare metabolic disorder characterized by near total or partial lack of subcutaneous adipose tissue and associated with insulin resistance. We aimed to evaluate the efficacy of magnetic resonance spectroscopy imaging (MRS) to explore the fat content of the liver in patients with lipodystrophy and to determine the relationship between the liver fat accumulation and clinical presentations of lipodystrophy. Materials and Methods: Between July 2014 and February 2016, 34 patients with lipodystrophy were assessed by MRS for quantification of hepatic steatosis. All patients had metabolic abnormalities associated with insulin resistance. Metabolic parameters and the MRS findings were analyzed to identify potential correlations between the liver fat content and disease severity. Results: The MRS fat ratios (MRS-FR) were markedly higher, indicating severe hepatic steatosis in lipodystrophy. Patients with generalized and partial lipodystrophy had comparable levels of MRS-FRs, although patients with generalized lipodystrophy were significantly younger. Patients with genetically based lipodystrophy had elevated MRS-FR compared to those with acquired lipodystrophy (p=0.042). The MRS-FR was positively correlated with liver enzyme alanine aminotransferase (p=0.028) and serum adiponectin (p=0.043). Conclusion: Our data suggest that MRS might be an effective, noninvasive imaging method to quantify hepatic fat content in patients with lipodystrophy. Further studies are needed to validate the technique and threshold values which would allow accurate comparison of data acquired by different machines and centers. Cite this article as: Altay C, Seçil M, Adıyaman SC, et al. Magnetic resonance spectroscopy to assess hepatic steatosis in patients with lipodystrophy. Turk J Gastroenterol 2020; 31(8): 588-95.